Polytherapeutic approach using bilayer matrix technology - Sharma, Sanjay Kumar; Mohan, Shailender; Jaimini, Manish; Tiwari, Rohit (Asian Journal of Pharmaceutics (AJP), 2014)
Oral administration of the drug is the most popular route for systemic effects owing to its ease of ingestion, pain, versatility, and most importantly, patient compliance. Combinational therapy have been found to have various advantages over monotherapy such as problem of dose-dependent side effects is minimized, a low‑dose combination of two different agents reduces the dose-related risk, the addition of one agent may counteract some deleterious effects of the other, using low dosage of two different agents minimize the clinical and metabolic effects that occur with maximal dosage of individual component of the combined tablet. Multilayer tableting is getting increasing attention from a variety of industries for a variety of reasons viz. patent extension, therapeutic, and marketing attendance. To reduce capital investment, quite often existing, but modified tablet presses are used to develop and produce such tablets. Although the general tablet manufacturing principles remain the same, there is much more to consider, since making multilayer tablets involves multiple often incompatible products, additional equipment, and many formulation and operation challenges. Key words: Bilayer matrix, combination therapy, multilayer tabletting, polytherapy